Ocupational health and safety in the Nigerian construction industry (2018)
Construction industry has been adjudged to be an important sector of any nation 's economy This sector has contributed to the growth of the economy and the physical development of the nation. However, the sector usually witnesses high occurrence of accidents and many hazards, especially, in Nigeria. Several issues have arisen on the challenges of occupational health and safety of workers in this industry. This paper examines the types of construction industry, its importance in Nigeria, various issues and perspectives relating to occupational health and safety of workers in the construction industry and also recommends cogent and radical Steps which must be taken to establish occupational health and safety of workers in the industry